Traditional Chinese Medicine Injections Combined With Oseltamivir for Influenza: Systematic Review and Network Meta-Analysis - Peng, Yingying; Chen, Zhe; Li, Huanmin; Han, Yaowei; Sun, Dan; Li, Yanjiao; Wu, Xiaoxia; Chen, Hongxiang; Li, Xinmin (Frontiers in Pharmacology, 2022)
Background: As a cause of respiratory tract infections in humans, influenza remains high morbidity and mortality, with associated significant healthcare burden and increased financial burden. Traditional Chinese medicine injections (TCMIs) combined with oseltamivir (TCMIs+oseltamivir) are the representative therapeutic strategies for influenza, which is compliant with clinical applications in China. To describe the comparative efficacy and safety of TCMIs+oseltamivir in patients with influenza, based on the current evidence. Methods: PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang Data Knowledge Service Platform, VIP information resource integration service platform databases, and Chinese biomedical literature service system, to find randomized controlled trials that TCMIs+oseltamivir for influenza, from inception until October 2021, without language restriction. Two investigators independently screened eligibility criteria, extracted data and appraised risk of bias with same criteria. We conducted network meta-analysis by Bayesian random method for each outcome and performed the sensitivity analysis, meta-regressions, and Egger’s and Begg’s tests for reliability and robustness of our results. Results: Thirty-one trials including 2893 participants proved eligible and reported on four TCMIs+oseltamivir versus oseltamivir. Network meta-analysis showed Xiyanping (XYP) +oseltamivir (OR = 5.9, 95% CrI: 3.1 to 11; SUCRA = 0.82) in response rate, Yanhuning (YHN) +oseltamivir (MD = -1.7, 95% CrI: -2.5 to -0.88; SUCRA = 0.89) in fever disappearance time, Tanreqing (TRQ) +oseltamivir (MD = -1.9, 95% CrI: -2.8 to -1; SUCRA = 0.97) in cough disappearance time, more efficacious than oseltamivir alone with the best SUCRA, respectively. Based on the combined SUCRA value for primary outcomes, TRQ+oseltamivir probably better in cough disappearance time, and XYP+oseltamivir and YHN+oseltamivir may better in fever disappearance time than others. No significant difference in safety between the treatments. Conclusion: In patients with influenza, TCMIs+oseltamivir may reduce cough and fever disappearance time, with no significant differences in harms. However, the safety remains uncertain, TCMI treatments for influenza should be considered with caution. More high-quality studies examining the efficacy and safety of TCMIs are needed.